Delegacia eletrônica da mulher como política pública para o enfrentamento da violência doméstica - Machida, Patrícia Pacheco Rodrigues (2023)
In this thesis, we explore the impact of technological innovations and social changes resulting from the digital age in the context of globalization for gender equality, with a focus on domestic violence and the role of the Maria da Penha Law as an affirmative and transformative tool in Brazilian society. The combination of technology and public policies can be a powerful tool in the pursuit of equality and justice in interpreting the Maria da Penha Law in light of its social objectives, linking it to the UN's Agenda 2030 and sustainable business practices based on ESG principles, contributing to a more equitable and just society. Companies play an important role in promoting women's rights, especially in combating domestic violence. The "Company and Human Rights" and "Women-Friendly Company" seals, as well as the "Hire More Women" program, strengthen the company's social commitment to addressing this issue, as they facilitate access to reporting channels, promoting a safer and more equitable environment for women. The objective is to understand how technological innovations enhance the effectiveness and efficiency of public policies for women victims of domestic violence, and the role of Electronic Police Stations, such as DDM Online, in this context. This allows victims to access justice, given that perpetrators, support networks, and technologies influence the prevention and addressing of violence. The methodology combined a literature review, document analysis, and jurisprudential research. Therefore, it can be concluded that the Electronic Women's Police Station has played a prominent role as a democratic public policy in combating violence against women, with the Maria da Penha Law and companies positively influencing the promotion of gender equality in protecting women.